Addressing the inequity of access to home Dialysis in Europe: recommendations for action informed by an international consensus exercise - Simon J. Davies; Bert Bammens; Ilaria de Barbieri; Edwina A. Brown; Jan van Cruchten; Dani Gallego; Eric Goffin; Maurizio Gallieni; Sotiroula Gliki; Jeroen P. Kooman; Gert Meeus; May-Britt Moeslund-Hansen; et al. (BMC Nephrology)
Abstract Background Use of Home Dialysis (referring to both peritoneal and home haemodialysis throughout this study), is under-exploited and highly variable across Europe, and this is the case both within as well as between countries. Several, predominantly modifiable barriers have been described that explain this inequity of access, but as yet no recommendations have been agreed upon as to how to address the problem. Methods A multi-disciplinary multi-organisational policy forum representing the key stakeholders was held at the EuroPD meeting in Bruges, November 2023 with the purpose of defining solutions and actions that the wider nephrology community should take to reduce disparities in access to home-based therapies. Three key themes were identified by a steering group prior to the forum: Dialysis Provider Motivation, Patient Empowerment and Training and Workforce Issues. Breakout discussion groups for each theme were asked to prioritise up to three actions per theme. These were further refined by the steering group and developed into proposed actions to be taken forward by the kidney failure community. Results 112 registrants attended the forum representing patients (5%), doctors, (57%) nurses, (13%) industry (7%) and various other roles (18%). The following actions were proposed: (1) a granular European audit of financial disincentives affecting decisions of policy makers, providers, patients and industry; (2) engaging national professional societies to challenge complacency towards uptake of home-based therapies; (3) stimulate networking to support small, inexperienced centres; (4) extending access to assisted peritoneal dialysis; (5) greater involvement of patients (locally and nationally) at every step, especially for advocacy; (6) empowering patients with transparent information; (7) mandating inclusion of training and exposure to Home Dialysis in national curricula; (8) promotion of career sub-specialists (doctors and nurses) with specific qualification in Home Dialysis; (9) promoting access to high quality training resources. Conclusions The kidney failure community can undertake a number of constructive actions to improve equity of access to Home Dialysis. The Policy Forum steering group who are representative of the key stakeholders have committed to taking this programme forward.